Theory and application of charge pumping for the characterization of Si-SiO/sub 2/ interface and near-interface oxide traps - Paulsen, Ron (IEEE Transactions on Electron Devices, 1994)
A generalized charge pumping model has been developed which extends the use of charge pumping from a study of traps at the Si-SiO/sub 2/ interface to a study of traps in the oxide. The analytical model, based on tunneling theory, allows the spatial distribution of near-interface oxide traps to be determined from variable frequency charge pumping data. Profiling of near-interface oxide traps in irradiated MOSFET's as well as SONOS nonvolatile memory devices is presented.